Implementation of Work From Home Policies During the Covid-19 Pandemic - Fahrani, Novi Savarianti (KnE Social Sciences, 2022)
The spread of Covid-19 since the beginning of 2020 has resulted in changes in the work system of Indonesian civil servants from working in offices to working from home (WFH). The goal of this was to break the chain of the spread of Covid-19. This was stated in the policy issued by the Minister of PAN RB which regulated this new WFH system of civil servants and was in accordance with the President’s policies related to accelerating the handling of the spread of Covid-19. This policy did not however apply to the two highest levels of structural officials in government agencies so that government administration and services to the community were not disrupted. This paper examined the implementation of WFH for civil servants who work in specific regions. Data were collected through interviews with relevant officials in the field of civil service in the district of North Sumatra Province, Kulon Progo Regency as a representation of the regional government agencies of the Sumatra Island region, Java, and the State Civil Service Agency as a representation of the central government agencies domiciled in the capital. This research was conducted in early 2021 as a form of evaluation of WFH implementation. It was found that those who work in WFH cities felt they had fewer days off than those who did not. Keywords: pandemic, Covid-19, new civil service work system, WFH, WFO, holidays